GOLD-DECORATED TITANIA NANOTUBES WITH GRAPHENE FOR VISIBLE LIGHT-MEDIATED AMOXICILLIN PHOTODEGRADATION - URDA, Alexandra; LAZAR, Diana; COSMA, Dragos; GROSU, Ion; SOCACI, Crina (Studia Universitatis Babeș-Bolyai Chemia, 2025)
The degradation of amoxicillin was accomplished using TiO2 nanotubes photocatalysts decorated with Au nanoparticles and containing reduced graphene or nitrogen-doped graphene under visible light exposure. The structural and morphological characterization confirmed the presence of gold nanoparticles and graphene, and the optical properties showed light absorption into visible region. The best results in the degradation of amoxicillin (up to 60%) were reached in the presence of the photocatalyst with nitrogen-doped graphene. A basics kinetic study showed a physical adsorption of the amoxicillin on the catalyst surface, and that the photodegradation step followed the pseudo-first kinetic model with the apparent kinetic constant of 0.0039 min-1.